1983
DOI: 10.1177/0013161x83019002006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Educational Program Proposals by Means of DEA

Abstract: A new application of DEA (Data Envelopment Analysis) is examined for evaluating the efficiency of occupational-technicalprograms in a comprehensive community college. This includes extensions of DEA for use in evaluating new programs that might be introduced along with possible combinations of old programs. Emphasis is placed on the relative efficiency aspects of DEA so that consequences for the efficiency ofprograms other than those being considered can be taken into account. Uses by the director of San Anton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…This led to the specific DEA method suggestion by Charnes, Cooper and Rhodes in 1978 [68]. Advantages of the increasing use in management research are the facts that no a priori existing knowledge of a production function is required, only real-life data is used (no hypothetical production function or efficiency values); and a multitude of inputs can be combined with a multitude of outputs, which is very typical for LSP as complex and high-level service providers as well as other service industries like health care or higher education [69][70][71][72][73].…”
Section: Efficiency Measurementmentioning
confidence: 99%
“…This led to the specific DEA method suggestion by Charnes, Cooper and Rhodes in 1978 [68]. Advantages of the increasing use in management research are the facts that no a priori existing knowledge of a production function is required, only real-life data is used (no hypothetical production function or efficiency values); and a multitude of inputs can be combined with a multitude of outputs, which is very typical for LSP as complex and high-level service providers as well as other service industries like health care or higher education [69][70][71][72][73].…”
Section: Efficiency Measurementmentioning
confidence: 99%
“…The underlying technique for efficiency measurement is the DEA introduced by Charnes, Cooper, and Rhodes [24] in the basic form with constant returns to scale (CRS) and extended by Banker, Charnes, and Cooper [25] with variable returns to scale (VRS). DEA applications within the higher education sector as a typical multi-input and multioutput production environment are numerous [26][27][28][29][30][31][32][33]. In addition, the Malmquist index for analysing longitudinal developments over time [34][35][36] has also been applied for universities, e.g., for the Philippines [37] and Australia [38].…”
Section: Introductionmentioning
confidence: 99%
“…Research papers in context with ESCM can be found in [2][3][4][5][6]. Literature is also available for the performance assessment of HEI in various countries all over the globe (USA [7][8][9][10][11], UK [12][13][14][15][16][17][18], Australia [19][20], China [21][22][23][24], India [25][26], Germany [27], Canada [28], Taiwan [29], Europe (30)(31), Spain [32], Russia [33], Turkey [34], Vietnam [35], Czech [36], Italy [37][38], Sweden [39], Mexico [40], Chile [41] and Greek [42]). The novelty of the present work lies in the inclusion of sustainability factors (Greenhouse gas emissions (GHG) in our case) while measuring the teaching and research efficiency.…”
Section: Introductionmentioning
confidence: 99%